2013
DOI: 10.1080/11250003.2012.738713
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the current distribution of free-living parrots and parakeets (Aves: Psittaciformes) in Italy: a synthesis of published data and new records

Abstract: Parrot species are often introduced outside of their native distribution range, as they are among the most popular pets worldwide. Releases, and particularly unplanned escapes, have resulted in the establishment of many naturalised populations in Europe, including Italy. Many parrot species present wide ecological tolerance and high synanthropy, but the knowledge of their distribution in the areas of introduction is limited. The introduction of these species may have a negative impact on local biodiversity, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 27 publications
1
40
1
2
Order By: Relevance
“…Rose-ringed parakeets also reportedly attack and kill little owls (Athene noctua) and red squirrels (Sciurus vulgaris) in Europe (Mori et al 2013b;. In possible defense of their nest, three rose-ringed parakeets killed an adult red squirrel (Japiot 2005).…”
Section: Range Of Damagementioning
confidence: 99%
“…Rose-ringed parakeets also reportedly attack and kill little owls (Athene noctua) and red squirrels (Sciurus vulgaris) in Europe (Mori et al 2013b;. In possible defense of their nest, three rose-ringed parakeets killed an adult red squirrel (Japiot 2005).…”
Section: Range Of Damagementioning
confidence: 99%
“…We assumed that those species might have established also in Selva di Paliano, as they have easily done elsewhere (cf. Lever 1987;Cosgrove 2003;Mori et al 2013), if not eradicated by poachers. Conversely, we considered as locally extinct those species that were introduced, migrated elsewhere and never returned to Selva di Paliano (Rodriguez-Cabal et al 2013).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The Alexandrine parakeet Psittacula eupatria, which occupies a natural range that extends from Afghanistan to Vietnam, including all of India, Sri Lanka and the Andaman Islands (Juniper & Parr, 1998), has been reported occasionally in Italy (Genoa, Reggio Emilia, Rome, Florence, Tigliole, AT,) (see AA.VV., 2015) but do not exist, based on the available data, cases of stable colonies nesting in the wild (Mori et al, 2013). The first sightings were recorded in Genoa in the years 1996-98 (Borgo et al, 2005) but then not have been more confirmed.…”
mentioning
confidence: 99%
“…comm. ) is now widespread in all urban green areas where it breeds regularly (Mori et al, 2013;Fraticelli, 2014). In addition, the Monk parakeet Myiopsitta monachus since its first reported colony in Rome in 1993, and its first nesting in 1996 (Cignini et al, 1996) is expanding gradually in various areas of the town (M. Maroni, pers.…”
mentioning
confidence: 99%
See 1 more Smart Citation